(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Rheological properties of asphalt S50 were improved by adding different prepared copolymers as additives with high homogeneity of asphalts samples. Three types of copolymers were prepared Poly (Indene –Co- maleic anhydride)(A1) Poly (Acrylonitrile –Co- Maleic anhydride) (A2) and Poly (Dipentine –Co-Maleic anhydride) (A3), the cross linking of (A3) to (A3d). by using sulfur. These copolymers were designed by inserting Maleic anhydride as rings containing through backbone of polymer chains to be high potentially to react with water to protect the crack of pavement .And moisture with inhibit bonding of crack of pavement, Many factors should be considered when prepared the additives to enhanced performance to be convenience cost, beneficial thermal safety , extended life of the asphalt, preparing conditions which gave high thermal resistance with more stabilities, all these prepared copolymer have been characterized by FTIR and H-NMR spectroscopies .Intrinsic viscosities were calculated. softening point and penetration were observed for all asphalts blends which were compared with the asphalt samples, which gave high thermal resistance with more stabilities. The results showed high properties of these blends when compared with the original asphalt. The physical properties of a specific polymers are determined by the sequence and chemical structure , When polymers are added to asphalt , the properties of the modified asphalt cement depend on polymer characteristic of asphalt and compatibility of polymer with asphalt. All these prepared copolymers were tested by softening points and penetration for all asphalt blends which were compared with the asphalt sample. All the Improvements made by adding polymers to asphalt included the Increasing the viscosity of the binder service, the thermal susceptibility of the binder, increased the cohesion of the asphalt, Increasing the resistance to permanent deformation, and Improved the resistance to fatigue at low temperatures, improved binder adhesion (higher viscosity of the binder)